2014
DOI: 10.1177/1535370214527903
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular adipose tissue-derived leptin promotes vascular smooth muscle cell phenotypic switching via p38 mitogen-activated protein kinase in metabolic syndrome rats

Abstract: Perivascular adipose tissue (PVAT)-derived leptin is a detrimental adipocytokine and plays a critical role in the development of cardiovascular diseases in metabolic syndrome (MetS). During vascular remodeling, vascular smooth muscle cells (VSMCs) undergo phenotypic switching into a synthetic phenotype characterized by decreased expression of differentiation markers (smooth muscle myosin heavy chain, α-smooth muscle actin, and calponin) and increased proliferation. We aimed to determine whether PVAT-derived le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 35 publications
1
30
0
2
Order By: Relevance
“…Interestingly, ROS may actually stimulate insulin sensitivity and improve metabolic homeostasis (30). In PAT, the adiponectin to leptin ratio has been shown to be cardioprotective with greater adiponectin and lower leptin being associated with improved endothelial function (23). Here, the adiponectin to leptin ratio was improved with Ex only.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, ROS may actually stimulate insulin sensitivity and improve metabolic homeostasis (30). In PAT, the adiponectin to leptin ratio has been shown to be cardioprotective with greater adiponectin and lower leptin being associated with improved endothelial function (23). Here, the adiponectin to leptin ratio was improved with Ex only.…”
Section: Discussionmentioning
confidence: 99%
“…The PVAT from the descending thoracic aorta of the mice was dissected and incubated with DMEM for 24 h. The medium was collected as conditioned medium (CM) [19]. In some experiments, PVAT-CM from different groups was pretreated first with palmitic acid (PA, 500 uM) or irisin (50 nM) and then pretreated with a varieties of inhibitors individually: HO-1 inhibitor stannous protoporphyrin (SnPP, 20 uM; Frontier Scientific, Inc., Logan, UT, USA), adiponectin receptor blocking peptide (ACRP-30 N-20, 0.4 μg/mL; Santa Cruz Biotechnology, USA), AMPK inhibitor Compound C (20 µM; Merck, Darmstadt, Germany) or eNOS inhibitor L-NAME (10 -4 M; Sigma) individually for 2 h. In brief, PVAT-CM was divided into different groups and a variety of inhibitors were individually added into the different groups.…”
Section: Methodsmentioning
confidence: 99%
“…Whereas collagen provides the aorta with mechanical strength (35), we found here that combining physical training with an HFD reduced the aortic content of these fibers [Figure 1F; p  < 0.05 (first and second analyses)]. Since this fact could be related to tissue remodeling, myofibroblasts were enumerated (36). Thus, we found that physical training increased the number of positive α-actin cells among rats that were fed an HFD [Figures 1G,H; p  < 0.05 (first analysis); p  < 0.001 (second analysis)].…”
Section: Resultsmentioning
confidence: 94%